Heart rate and mortality in myocardial infarction: incremental or bimodal correlation?. (3rd October 2022) - Biasco, L; Foster-Witassek, F; Radovanovic, D; Dittli, P; Tersalvi, G; Rickli, H; Roffi, M; Eberli, F; Jeger, R; Erne, P; Pedrazzini, G B
Abstract: Introduction: Risk prediction scores adopted in acute coronary syndromes use incremental models to estimate mortality for heart rate (HR) above 60 bpm. Nonetheless, a non-linear, bimodal relationship, with higher event rates at low or high HR, has been described, potentially hampering risk prediction accuracy. Purpose: Our aim was to assess the prognostic impact of bradycardia, defined as admission HR <50 bpm, in myocardial infarction (MI) among patients enrolled in a large nationwide registry. Methods: Data of patients enrolled between 1999 and 2021 stratified by admission HR were retrospectively analysed. The primary endpoint was in-hospital mortality. The secondary endpoint was a composite of death, cerebrovascular event, and reinfarction. Associations between HR and outcomes were assessed at univariate and multivariable logistic regression analyses, then verified after sequential propensity-score matchings among HR groups. Results: 51001 patients (median age 66 years, IQR 56–76) were included. Crude estimates showed a bimodal distribution of primary and secondary endpoints with peaks at low and high HR. Association of HR <50 bpm with mortality was recognised only at primary multivariable logistic regression analysis (OR 1.49; 95% CI 1.01–2.13 p=0.038) but not at multiple sensitivity analyses after exclusion of patients on negative chronotropic therapy. Three sequential propensity-score matching were performed among patients with HR <50 bpm at admission and those with HR 50–75 bpm, HR 76–100 bpm and HR >100 bpm at admission, identifying 1159, 1159 and 1158 matched pairs, respectively. After propensity-score matching, rates of primary and secondary endpoints equalled among groups with HR <100 bpm. Conclusions: Bradycardia (HR <50 bpm) at admission in patients with MI identified a group with higher crude rate of adverse events. Nonetheless, the signal supporting an independent association between bradycardia at admission and short-term mortality is weak and was not confirmed after correction for relevant baseline differences by propensity score matching. These findings support the hypothesis that lower HR might not be causative for the worse outcomes, but rather serves as a marker of underlying morbidity. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): The AMIS Plus registry is funded by unrestricted grants from the Swiss Heart Foundation and from Abbot AG, Amgen AG, AstraZeneca AG, Bayer (Schweiz) AG, Biotronik AG, Boston Scientific AG, B. Braun Medical AG, Daiichi-Sankyo/Lilly AG, Cordis Cardinal Health GmbH, Medtronic AG, Novartis Pharma Schweiz AG, Sanofi-Aventis (Schweiz) AG, SIS Medical AG, Terumo AG, Vascular Medical GmbH, all in Switzerland, and the Swiss Working Group for Interventional Cardiology. The sponsors did not play any role in the design, data collection, analysis, or interpretation of data.